Perceived leadership style as a mediator of the relationship between training management influences and self-assessed job performance: Training management for mentors in Guangdong higher education - Dan, Li; Keat, Ooi Boon (Edelweiss Applied Science and Technology, 2025)
This study examines the mediating role of perceived leadership style (PLS) in the relationship between training management influences and self-evaluation of job performance (SJP) among university mentors in Guangdong, China. This research utilized a random sampling survey method; mentors were randomly selected from 164 higher education institutions in Guangdong Province, China. An online questionnaire was administered to participants for data collection, ensuring no missing data. A total of 489 participants responded effectively from the 550 distributed questionnaires. Grounded in Path-Goal Theory (PGT), the research investigates how mentors’ individual factors, training motivation, and organizational rewards influence SJP, with PLS as a mediator. Training management factors (individual competencies, motivation, and rewards) significantly enhance SJP, corroborating prior research on training effectiveness. Perceived leadership style partially mediates these relationships, with the strongest mediation effect observed between training motivation and SJP (36.3% mediation ratio). Directive and supportive leadership styles were particularly influential in shaping mentors’ performance evaluations. The study contributes to leadership and human resource management literature by validating PGT in Chinese higher education and highlighting the critical role of adaptive leadership in mentor training. Practical implications include recommendations for universities to refine leadership development programs and address regional and gender disparities in mentorship opportunities. Future research should expand to diverse geographical contexts and employ longitudinal designs to strengthen causal inferences.